2022
DOI: 10.3389/fnbeh.2022.850623
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen, the Peripheral Immune System and Major Depression – A Reproductive Lifespan Perspective

Abstract: Major depression is a significant medical issue impacting millions of individuals worldwide. Identifying factors contributing to its manifestation has been a subject of intense investigation for decades and several targets have emerged including sex hormones and the immune system. Indeed, an extensive body of literature has demonstrated that sex hormones play a critical role in modulating brain function and impacting mental health, especially among female organisms. Emerging findings also indicate an inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 274 publications
(376 reference statements)
0
4
0
Order By: Relevance
“…As previously mentioned, fluctuations in endogenous estrogen levels are pivotal in the pathogenesis of depression in women [ 47 ]. Rapid changes in E2 levels can heighten the susceptibility to depression in women [ 48 , 49 ]. Furthermore, when the brain is exposed to low levels of E2, women must rely on multiple pathways to adapt to the lack of circulating estrogen to maintain central nervous system homeostasis [ 50 ].…”
Section: Estrogen Receptors and Related Signaling Pathwaysmentioning
confidence: 99%
“…As previously mentioned, fluctuations in endogenous estrogen levels are pivotal in the pathogenesis of depression in women [ 47 ]. Rapid changes in E2 levels can heighten the susceptibility to depression in women [ 48 , 49 ]. Furthermore, when the brain is exposed to low levels of E2, women must rely on multiple pathways to adapt to the lack of circulating estrogen to maintain central nervous system homeostasis [ 50 ].…”
Section: Estrogen Receptors and Related Signaling Pathwaysmentioning
confidence: 99%
“…Hormonal, psychological, and immunological factors in menopause can interact and infl uence each other. Hormonal changes, such as the decline in estrogen levels, can aff ect psychological well-being and immune function [67]. Psychological factors, such as stress, anxiety, and mood disturbances, can modulate hormonal and immune responses.…”
Section: Effects Of Hormonal Psychological and Immunological Factors ...mentioning
confidence: 99%
“…Moreover, there are studies that PMDD may predict perintal depression (mostly postpartum), and that this association may be attributed to genetic similarities as well as to sex hormonal pathways ( McEvoy et al, 2017 ; Pope et al, 2017 ). As such, PMS, AD, and PPD may share common immune-inflammatory and sex hormonal pathways ( Engler-Chiurazzi et al, 2022 ; Lombardo et al, 2021 ); therefore, clinical associations between both conditions may be anticipated. However, most of the current studies focus on associations between PMS and PPD ( Pereira et al, 2022 ), and only few studies have shown that women with PMS symptoms showed increased risk towards AD ( Sugawara, 1997 ; Pataky & Ehlert, 2020 ).…”
Section: Introductionmentioning
confidence: 99%